(untitled) (Jurnal Bahasa, 2004)
The Indonesian and the Malaysian are normally seen as two ’twin’ - languages which are similar but not the same. The article aims at exploring phenomena which are not the same regarding prepositions and conjuctions in the two languages. From the theoretical point of view, subgroupping of prepositions and the controversial question of distinguishing the two categories of function words are considered. The comparative study involves both quantitative and qualitative aspects with focus onfungsional properties, though the semantic aspect is also touched upon.